The Study on Influence of the Method of Handling of Measuring Head on Measurement Results Obtained with the Use of a Portable Profilometer - Krzysztof Stępień; Stefan Talu (Tehnički Vjesnik, 2019)
Portable profilometers are very common in industrial practice. In particular, they are useful if one wants to perform in-situ inspection of surface roughness under industrial conditions. They are usually small and light and owing to that they are portable and this is why they can be applied under industrial conditions. However, there are numerous factors that influence results of in-situ surface roughness measurements. One of such factors is a human error, since the measuring head is usually controlled manually by an operator. The paper presents results of the research aiming at establishing if there is statistically significant difference between results obtained for mechanical or manual handling of measuring head. In the experiments the following parameters were analyzed: Ra, Rq, Rt and RSm.